Evaluation of a surveillance system for Clostridioides difficile infections for Swiss hospitals (Swiss Medical Weekly, 2024)
AIMS:This study evaluated an approach to establishing a comprehensive nationwide surveillance system for Clostridioides difficile infection in Switzerland. We report the results of patient-related surveillance and calculate the incidence rate of C. difficile infection in Switzerland in 2022.METHODS: Initiated in 2017 by the National Centre for Infection Prevention (Swissnoso), in collaboration with the Swiss Centre for Antibiotic Resistance (ANRESIS), laboratory surveillance enables the automatic import of C. difficile infection laboratory data and is fully operational. However, the very limited number of participating laboratories impedes the generation of representative results. To address this gap, Swissnoso introduced patient-related surveillance, with a questionnaire-based survey used across Swiss acute care hospitals.RESULTS: This survey revealed an incidence of 3.8 (Poisson 95% CI: 3.2–4.5) C. difficile infection episodes per 10,000 patient-days, just above the mean rate reported by the European Centre for Disease Prevention and Control (ECDC). Additionally, we report substantial heterogeneity in laboratory tests, diagnostic criteria and infection control practices among Swiss hospitals.CONCLUSION: This study underscores the importance of a joint effort towards standardized surveillance practices in providing comprehensive insights into C. difficile infection epidemiology and effective prevention strategies in Swiss healthcare settings. The patient-related approach remains the gold standard for C. difficile infection surveillance, although it demands substantial resources and provides results only annually. The proposed implementation of nationwide automated laboratory-based surveillance would be pragmatic and efficient, empowering authorities and hospitals to detect outbreaks promptly and to correlate infection rates with antibiotic consumption.